Can We Increase Sugar Beet Yield with Lime, Cultivar Selection, and Fertilizer Applications?. Issue 1 (28th April 2017) - Chatterjee, Amitava; Cattanach, Norman
Abstract : Core Ideas: Lime and cultivar had no effect on sugar beet production. Liquid starter can reduce the seed germination. Recommended fertilizer application is enough for fields with history of sand syndrome.